1999
DOI: 10.1139/v98-219
|View full text |Cite
|
Sign up to set email alerts
|

Heterocyclic aromatic amide protecting groups for aryl and phthalocyaninesulfonic acids

Abstract: Pyroles, indole, imidazole, and a pyrazole were treated with 3,4-dibromobenzenesulfonyl chloride to form 3,4-dibromobenzenesulfonamides. The l-(3,4-dibromophenylsulfonyl)pyrrole and I -(3,4-dibromophenylsullonyl)indole were stable to CUCN iu DMF to produce l{3,4-dioyanophenylsulfonyl)pynole and l-(3.4-dicyanophenylsulfbnyl)indole, which upon treatment rvith ammonia in 2-N,,V-dimethylaminoethanol gave the protected phthalocyanine-2,9,16,23-tetrasulfonamides. Base cleavage of these sulfonamides yielded the free … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…Compound 2 (0.83 g (77 % purity), 5.03 mmol) was added. : [53] Ethylene glycol-1,2-bis(3,4-dibromobenzenesulfonate) (5 c): Potassium trimethylsilanolate (1.92 g, 14.96 mmol) was added as a solid in portions to a solution of ethylene glycol (0.19 g, 2.99 mmol) and 4 (2.5 g, 7.48 mmol) in THF (6 mL) under ice cooling. The combined organic layers were washed with H 2 O (30 mL) and brine (30 mL), then dried over Na 2 SO 4 .…”
Section: N-(benzyloxycarbonyl)-(o-(2-fluoroethyl)tyrosine)-methylazalmentioning
confidence: 99%
See 1 more Smart Citation
“…Compound 2 (0.83 g (77 % purity), 5.03 mmol) was added. : [53] Ethylene glycol-1,2-bis(3,4-dibromobenzenesulfonate) (5 c): Potassium trimethylsilanolate (1.92 g, 14.96 mmol) was added as a solid in portions to a solution of ethylene glycol (0.19 g, 2.99 mmol) and 4 (2.5 g, 7.48 mmol) in THF (6 mL) under ice cooling. The combined organic layers were washed with H 2 O (30 mL) and brine (30 mL), then dried over Na 2 SO 4 .…”
Section: N-(benzyloxycarbonyl)-(o-(2-fluoroethyl)tyrosine)-methylazalmentioning
confidence: 99%
“…The solvent was removed in vacuo and the remaining residue was purified by vacuum distillation (0.038 mbar, 120 8C) to obtain 4 (2.96 g, 77 %) as a yellowish waxy solid; mp: 38-40 8C (lit. : [53] Ethylene glycol-1,2-bis(3,4-dibromobenzenesulfonate) (5 c): Potassium trimethylsilanolate (1.92 g, 14.96 mmol) was added as a solid in portions to a solution of ethylene glycol (0.19 g, 2.99 mmol) and 4 (2.5 g, 7.48 mmol) in THF (6 mL) under ice cooling. The reaction mixture was stirred for 2 h in the ice bath and subsequently diluted with ice-cold H 2 O (30 mL) and CH 2 Cl 2 (20 mL).…”
Section: Syntheses Of Reference Compounds and Precursorsmentioning
confidence: 99%
“…Using such starting material will still produce mix PCs with sulphonic groups on either α-or β-positions [25]. Using pure 4-sulphonic fragments can ensure the sulphonic groups on β-positions [10,26,27]. However, isomers still existed due to the different arrangement patterns of substituents on the PC macrocycle.…”
Section: Introductionmentioning
confidence: 99%
“…Leznoff et al reported zinc sulfonamidophthalocyanines with N-heterocyclic aromatic protecting groups for sulfonic acids in the view of their potential as photodynamic therapy agents against cancer tumors [29]. A sulfonamide linkage was also used for the covalent attachment of metallophthalocyanines to a silica support [14,30,31] and very recently we have reported the synthesis of metallophthalocyanines linked to organic copolymers and their high efficiency as supported oxidative catalysts [32].…”
Section: Synthesis Of Metallo-tetrasulfonamidophthalocyaninesmentioning
confidence: 99%